Hubungan Pengetahuan Dengan Kesiapan Mahasiswa Keperawatan Ende Dalam Melakukan Bantuan Hidup Dasar (BHD) - Maria Salestina Sekunda; Anatolia K Doondori; Theresia Avila Kurnia; Try Ayu Patmawati (Jurnal Keperawatan Muhammadiyah, 2022)
Objective:  to analyze the effect of knowledge on the readiness of nursing students to perform basic life support in the Ende Nursing Study Diploma III ProgrammeMethods: this research is correlational non-experimental with a cross sectional time approach to determine the effect of nursing students' knowledge and readiness in performing basic life support. The sample in this study were 44 students who met the following criteria: 1) Level III students who were registered as diploma nursing students, 2) Willing to be partisipated in this research. The sample in this study were nursing students level III semester V totaling 44 people. In this research, the sampling technique used  is total sampling. Data analysis using statistical analysis.The results showed that 68% of respondents had good knowledge of BLS and 70% of respondents were ready to do BLS. There is an influence of respondents' knowledge and readiness in doing BLS with p value = 0.03 (95% CI 1.121-10.480). Therefore, it is necessary to conduct further research on the skills of nursing students in carrying out BLS so that they can provide first aid in cases of cardiac arrest outside the hospital and improve survival.Conclusion:  There is a correlation of knowledge with the readiness of nursing students in doing BHD